Over-representation of myocardial infarction with nonobstructive coronary arteries in oncological patients. The prevalence, clinical characteristics and long-term mortality. (25th November 2020) - Stepien, K; Nowak, K; Szlosarczyk, B; Stepien, A; Nessler, J; Zalewski, J
Abstract: Introduction: According to the current guidelines, myocardial infarction with nonobstructive coronary arteries (MINOCA) is defined by general criteria of myocardial infarction (MI) with no hemodynamically significant lesions in coronary arteries (<50%). As shown in large MI registers, MINOCA is diagnosed in 1–13% of patients. The potential etiology of MINOCA is an intensively studied issue. To date, a number of potential mechanisms have been proposed. In our opinion, hypercoagulable states may be indicated as a direct trigger for such a sequence of events. Based on our previously published study, we found the presence of inherited thrombophilia in over 23.8% of MINOCA patients Purpose: We suspect that oncological patients, the group with well-known prothrombotic state, are predisposed to MINOCA and have different clinical characteristics and long-term prognosis. Methods: We analyzed a group of 1011 consecutive patients with MI who underwent coronary angiography in the years 2012–2017. A group of 134 patients with active cancer (13.3%) was separated. Working diagnosis of MINOCA was performed in accordance with current guidelines. Results: MINOCA diagnosis was stated in 21 oncological patients (15.7%) and 51 others (5.8%) (P<0.001). Cancer patients were characterized by a higher incidence of anemia (47.6 vs 21.6%, P=0.027), lower hemoglobin levels (12.9 vs 14.1 g/dl, P=0.048) and higher troponin values (0.306 vs 0.076 ng/ml, P=0.003). Based on echocardiographic measurements, more frequent occurrence of takotsubo cardiomyopathy (19.1 vs 2.0%, P=0.010), higher values of right ventricular systolic pressure (44.5 vs 31.5 mmHg, P=0.016) and lower left atrial dimensions (36 vs 41.5 mm, P=0.020) were observed in the group of cancer patients. As expected, patients with active cancer had significantly higher all-cause mortality during long-term follow-up (66.7 vs 29.4%, P=0.003). In a multivariable analysis of oncological MINOCA was independently associated with a long-term mortality (P<0.001). Conclusions: To our knowledge, our study is the first report concerning a high prevalence of MINOCA in oncological patients with MI. We observed a significant proportion of cancer-associated anemia in this group of patients. The high incidence of takotsubo cardiomyopathy and significant differences in individual echocardiographic parameters underline the important role of cardiac imaging in this group of patients with unfavorable long-term prognosis. Funding Acknowledgement: Type of funding source: None